Recommendations for hypolipidemic and antithrombotic therapy in HCV-infected patients treated with direct-acting antiviral agents: expert position statement - Jaroszewicz, Jerzy; Broncel, Marlena; Piekarska, Anna; Szymanski, Filip; Tomasiewicz, Krzysztof; Rajewski, Paweł; Banach, Maciej; Hudzik, Bartosz; Gąsior, Mariusz; Flisiak, Robert; Gil, Robert (Clinical and Experimental Hepatology, 2025)
The recently observed increase in cardiovascular disease incidence in patients with chronic hepatitis C has contributed to hepatitis C virus (HCV) being considered a new, non-classical risk factor. HCV infection may also lead to the development of metabolic disorders, which play an important role in the development of cardiovascular diseases. The notable impact of HCV on the development of obesity, insulin resistance, diabetes, lipid disorders and fatty liver has led to metabolic disorders in the course of HCV infection being referred to as metabolic-viral syndrome. On the other hand, modern treatment of HCV infection with direct-acting antiviral drugs is extremely effective and safe, while drug interactions are the main potential limitation. This article presents expert recommendations for the diagnosis and treatment of heart disease and lipid disorders in HCV-infected patients.